1990
DOI: 10.1007/bf00340142
|View full text |Cite
|
Sign up to set email alerts
|

L5 radicular pain related to lumbar extradural gas-containing pseudocyst

Abstract: L5 radicular pain related to an epidural gas-containing pseudocyst is described in a 62-year-old female. Transient resolution of radicular pain was observed after CT-guided gas aspiration. Recurrent radicular pain led to surgical treatment; after operation the radicular pain disappeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 5 publications
0
35
0
4
Order By: Relevance
“…CT-guided aspiration may be possible, but recurrences have been reported. 1,3) As our patient had no pain relief with conservative therapy, he underwent removal of the herniated disc containing gas at both regions via different approaches with excellent pain relief postoperatively.…”
Section: Discussionmentioning
confidence: 88%
“…CT-guided aspiration may be possible, but recurrences have been reported. 1,3) As our patient had no pain relief with conservative therapy, he underwent removal of the herniated disc containing gas at both regions via different approaches with excellent pain relief postoperatively.…”
Section: Discussionmentioning
confidence: 88%
“…Recurrence of a gas pseudocyst was reported after CT-guided percutaneous needle aspiration or surgery with needle aspiration 2,3,10) . The patient in the present study underwent complete decompression and fusion to remove the lesion because she showed severe neurologic deficit.…”
Section: Case Reportmentioning
confidence: 99%
“…However, in that case, the gas pseudocyst was connected to the L2-L3 intervertebral disc, which contained intradiscal gas; which differs from the present case. Bosser et al 2) reported L5 radicular pain related to a lumbar extradural gascontaining pseudocyst that was treated by CT-guided aspiration. Different from these prior cases, this case with a foraminal gas pseudocyst that was associated with a sudden foot drop, which Fig.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of gas in the spinal canal, with or without disc material, causing nerve root compression [2][3][4][5]8,12,14,16) . However, gas-filled intradural cysts are rare.…”
Section: Introductionmentioning
confidence: 99%